Contributing Factors for a Late Spontaneous Peripherally Inserted Central Catheter Migration: A Case Report and Review of Literature. Issue 3 (May 2015) - Beccaria, Paolo; Silvetti, Simona; Mucci, Milena; Battini, Ivana; Brambilla, Paola; Zangrillo, Alberto
Purpose: Peripherally inserted central catheters (PICCs) are associated with some adverse events, the most frequent are thrombosis, tip catheter malposition and spontaneous late migration. However, the cause of spontaneous late migration in most cases remains unknown. We carried out this study to add data to the literature on PICCs late spontaneous migration. Methods: We conducted a systematic review of all manuscripts describing PICC spontaneous late migration in adult populations and we also described two cases of late PICCs migration. Results: We identified five studies for a total of 58 cases of PICC late migration. In our two cases, patients' activity is an important contributing factor for late spontaneous PICC migration. Conclusions: To avoid late catheter misplacement, initial malposition should be immediately identified and promptly corrected and a detailed patients training should be carried out.